(untitled) (Bangladesh Journal of Microbiology, 2019)
The rapid dissemination of antibiotic resistant E. coli is now a worldwide problem. In this study, a total of twenty E. coli obtained from stool were selected to determine resistance to beta lactam antibiotics. Beta–Lactamase are enzymes produced by bacteria that provide multi resistance to beta lactam antibiotics such as penicillin, cephalosporin, cephamycin and carbapenems. Of these isolates (n = 20), 35% were found resistant to Amoxicillin Clavulanate, 5% to Imipenem, 50% to Ceftriaxone and 75% to Ampicillin. PCR amplification confirmed the presence of the New Delhi beta-lactamase gene (blaNDM) in one isolate (5%, n=20). Plasmids of variable sizes were found in all the isolates. Beta lactam antibiotics are now commonly used for the treatment of disease. Resistance of 50% of the isolates to Ceftriaxone is alarming as this indicates that an alternative drug may soon need to replace this antibiotic for successful treatment. The finding of this study is also of public health concern as plasmids were found in most isolates and these mobile genetic elements can be transferred among clinical bacteria, thereby disseminating antibiotic resistance further limiting treatment options. Bangladesh J Microbiol, Volume 36 Number 1 June 2019, pp 29-33